Novel Method for the Synthesis of Substituted Imidazothiazolones - Kravchenko, Angelina N.; Antonova, Maria M.; Baranov, Vladimir V.; Nelyubina, Yulia V. (Synlett, 2015)
A general and highly selective method for the synthesis of 4-substituted 3a,6a-diphenyltetrahydro-2H-imidazo[4,5-d][1,3]thiazole-2,5(3H)-diones has been developed through a new reaction of 1-substituted 5-hydroxy-4,5-diphenyl-1Н-imidazol-2(5Н)-оnes with potassium thiocyanate in the presence of acetic acid in acetonitrile. Details of supramolecular organization in the crystalline imidazothiazolones, as revealed by X-ray diffraction, are highlighted.
Keywords: cyclocondensations; potassium thiocyanate; heterocycles; polycycles; imidazolоnes; imidazothiazoles